Internet marketing bugs: victims of personalization - Kolodiuk, Svitlana; Shchehlova, Alla (My University, 2020)
Every day mankind struggles with many serious problems, which significantly affects the quality of life of entire generations. Modern problems require modern solutions. Personalization of marketing has become a lifeline for the digital era, but not everything has gone according to plan. It is an effective tool for business in capable hands, but also personalization began to associate with an annoying element for many of us. There were identified some mistakes in the personalization of the marketing industry based on reputable statistical agencies' research. High-quality targeting is the main personalization goal. For present advertising campaigns are like a set of random information thanks to unscrupulous specialists. It has irritated the audience and made the surviving more difficult for business. The situation has the property to become worse and creates new difficulties for solving. Large companies professionals make great efforts to avoid discrimination and other aspects of tolerance that the public pays a big piece of attention. Many businesses are litigated by minorities because of their controversial campaigns and the targeting approach. Researches show that highly paid ads on Facebook and Google are much more often shown by business to men, and it is a shadow of discrimination by gender. Social platforms algorithms are a very important part of the global system, as automatic settings help to stabilize and resolve such problems for society and business. But many people try to avoid them and create a set of conflict situations that require the constant presence of a live moderator that is impossible for the present. That is why companies need to have not only a strong marketing specialist but also an in-house lawyer in the current business environment. Щодня людство бореться з багатьма серйозними проблемами, які істотно впливають на якість життя цілих поколінь. Сучасні проблеми вимагають сучасних рішень. Персоналізація маркетингу стала рятівним кругом для цифрової ери, але не все йде за план. Цей ефективний інструмент для бізнесу в умілих руках, але персоналізація стала асоціюватися у багатьох з нас з дратівливим елементом. На підставі досліджень авторитетних статистичних агентств були виявлені деякі помилки в персоналізації індустрії маркетингу. Головною метою персоналізації є якісне таргетування. На сьогодні рекламні кампанії подібні до набору випадкової інформації завдяки недобросовісним фахівцями. Це дратувало аудиторію і ускладнювало виживання для бізнесу. Ситуація стає все гірше і створює нові труднощі для вирішення. Професіонали великих компаній докладають великих зусиль, щоб уникнути дискримінації інших аспектів толерантності, яким громадськість приділяє велику увагу. Багато підприємств піддаються критиці меньшинами у зв'язку з їх суперечливими кампаніями і цілеспрямованим підходом. Дослідження показують, що високооплачувана реклама на Facebook і Google набагато частіше показується бізнесом чоловікам, що є тінню дискримінації за статевою ознакою. Алгоритми соціальних платформ є дуже важливою частиною глобальної системи, оскільки автоматичні налаштування допомагають стабілізувати і вирішити такі проблеми для суспільства і бізнесу. Але багато хто намагається їх уникнути і тим самим створює ряд конфліктних ситуацій, що вимагають постійної присутності живого модератора, що наразі неможливо. Саме тому компаніям необхідно мати не лише сильного фахівця з маркетингу, але і штатного юриста в сучасному бізнес середовищі.
Keywords: advertising campaigns; marketing; personalization; targeting; information; customer; business; discrimination; кафедра ділової іноземної мови та міжнародної комунікації; маркетинг; персоналізація; таргетинг; інформація; клієнт; бізнес; дискримінація; рекламні кампанії